2021
DOI: 10.3390/agronomy11102051
|View full text |Cite
|
Sign up to set email alerts
|

Management of Iron and Manganese Toxicities of Lentil Crops Grown in Central Chile

Abstract: Iron (Fe) and manganese (Mn) toxicity is a widespread problem in lentil production in the coastal dryland of Chile. Increasing the soil pH by liming with CaCO3 or incrementing grain yields through nitrogen fertilization can help the plants to reduce metal concentration. Thus, the main objective of this work was to evaluate two different fertilization strategies (lime (CaCO3) and nitrogen (N) additions) to reduce Fe and Mn toxicities in lentils. Lentils grown under field conditions with the highest Fe and Mn co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…These findings were in agreement with those of Ibrahim et al (2019), who indicated that N application in salty soils is indicated as improving plant growth parameters. Also, similar result was reported by Amigo et al (2021), who noticed that N fertilization increased DM production of lentils and reduce Fe and Mn concentrations on leaves to a level that is possibly under the threshold that causes toxicity in plant tissues. Furthermore, saline soil can change the role of N in plants metabolism.…”
Section: Discussionsupporting
confidence: 87%
“…These findings were in agreement with those of Ibrahim et al (2019), who indicated that N application in salty soils is indicated as improving plant growth parameters. Also, similar result was reported by Amigo et al (2021), who noticed that N fertilization increased DM production of lentils and reduce Fe and Mn concentrations on leaves to a level that is possibly under the threshold that causes toxicity in plant tissues. Furthermore, saline soil can change the role of N in plants metabolism.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, due to the possible symbiotic binding of N 2 by legumes and the resulting release of H + into the rhizosphere, acidification of the rhizosphere occurs (Amigo et al., 2021). Combining these processes, it can be assumed that the cultivation of legumes may result in an increased availability of Fe and Mn in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…However, not all forms of Fe and Mn are available to crop plants. According to Amigo et al (2021), in particular, soil redox potential and pH determine the availability of Fe and Mn to plants. The authors also point out that by changing the redox potential by replacing soil oxygen with nitrogen gas, there was an increase in Fe and Mn soil solubility of several folds.…”
mentioning
confidence: 99%